Advancing Educational Practices: Implementation and Impact Desain Grafis in Education - Iskandar, M. Yakub; Azira, Voni; Nugraha, Ridho Aprilia; Jasneli, Icha; Rahmanda, Rega; Putra, Andri Eka (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
Tutorial videos have an important role in supporting the learning process in class. Teachers predominantly use whiteboard media so that students need help understanding the material presented because the learning process is still teacher-centered. The need for appropriate learning media such as video tutorials makes the learning process student-centered. The research aims to develop valid and practical video tutorial learning media. The research method is R&D (Research and Development) by Borg and Gall this model stage was modified into five steps, namely initial product development planning, product validation, limited trials, and final product. The material validity results were 4.53 in the